The determinants of bank profitability Empirical evidence from the Chinese banking sectors - Li, Jiaping (2019)
The purpose of this paper is to investigate the influence of bank-specific and macroeconomic determinants of bank profitability through the System Generalized Method of Moments (System-GMM). This paper applies a dynamic panel of top 100 Chinese commercial banks over the period of 2011-2018. This period is the highly implement of reform and the substantial advancement of Internet Finance, which exerts a significant impact on bank profitability. This results show that credit risk, operating efficiency and bank size have a negative and significant influence on bank profitability, while capital adequacy and liquidity risk exert positive correlation with bank profitability. As for macroeconomic factors, the GDP growth rate and Internet Finance positively and significantly effect on bank profitability, while inflation rate is positively related on bank profitability. Among all variables, capital adequacy and inflation rate is not significant associated with bank profitability.